Cytological diagnosis of transmissible venereal tumour in a dog - A report (Indian Journal of Veterinary Pathology, 2025)
A six months old mongrel dog was presented at Sanchu Animal Hospital, Velachery, Chennai for diagnosis and treatment with a history of bleeding from the prepuce and presence of cauliflower like growth on the penile region. Physical examination of the affected dog showed numerous cauliflower growths around the bulbus glandis of the penis. Haematological examination revealed mild leukocytosis accompanied by mild neutrophilia and eosinophilia. Cytological examination of impression smears taken from the mass revealed the presence of numerous discrete round cells with characteristic cytoplasmic vacuolations, suggestive of transmissible venereal tumour. Based on the laboratory findings, the affected dog was treated with vincristine sulphate along with multivitamin syrup and herbal liver tonic. The treated dog showed marked regression in growth after two weeks of treatment. Thus, the present study reports a case of transmissible venereal tumour based on the cytological examination of nodules present on the penile region of a dog.